Do pharmaceuticals affect microbial communities in aquatic environments? A review - Świacka, Klaudia; Maculewicz, Jakub; Kowalska, Dorota; Grace, Michael R. (Frontiers in Environmental Science, 2023)
Pharmaceuticals have been identified as a significant threat to the environment. Their constant flow into aquatic ecosystems means that organisms are chronically exposed. To date, there has been a large number of scientific papers assessing the impact of pharmaceuticals on individual organisms from different taxonomic groups. However, the effects of drugs on the environment can be much broader than what can be determined in toxicity tests on individual organisms. These compounds can disrupt entire communities. In this context, special attention should be paid to microbial communities, which regulate many essential processes underpinning aquatic food webs and ecosystem services. This paper reviews current developments related to the effects of pharmaceuticals on microorganisms with a particular focus on whole-community investigations, in both fresh and salt water. We also summarize the opportunities associated with both in situ and laboratory studies, and highlight important knowledge gaps.